Social Consciousness and Indifferent Business Postures - Subramanian, K. R. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Businesses are created, sustained and expanded to gain more profit to the stake holders particularly the business owners. Social Responsibility of Business is talked about loudly, but there is lack of awareness of ‘Social Consciousness’. At the grass root level business practices are in line with unscrupulous political and bureaucratic maneuvers to make a fast buck out of any situation of discomfort of people at large. Social consciousness of business is of recent origin and many American and foreign businesses are aware of the importance of this. India, which has contributed so much by Vedic and Upanishad literature to raise the level of consciousness has not lived up to raising consciousness of business to this level. The recent example is the ‘Fire’ accident at the Chennai silks building. An estimated one million Liters of water was consumed to control the fire at the cost of starving the parched city dwellers and depriving them of drinking water. When the whole city is reeling under shortage of drinking water is it not a moral responsibility of the owners of business to make some alternate arrangements or at least offer an apology? Where is the social consciousness gone? The subject matter of this article is the ‘Social Consciousness’.